Needfulness and the Knowledge of God in Barth’s Dogmatics - Dorman, David A. (Journal of reformed theology, 2024)
In the opening of CD II/1, Barth expounds his theological epistemology anchored in the grace of God and (thereby) the concomitant readiness of humanity for grace. In doing so he propounds a “Christian anthropology” of “blessed radical needfulness” that explicates God’s creational intention for humanity, the turn of humanity to sin, and humanity’s redemption in Jesus Christ. Although the significance of this positive anthropological proposal has suffered in critical discussion, a renewed look at its function discloses it to be decisive for Barth’s understanding of how we as humans know God and how we understand ourselves and/or salvation.